2011
DOI: 10.1590/s0104-07072011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Carga de trabalho de enfermagem em unidade de terapia intensiva de cardiologia e fatores clínicos associados

Abstract: O estudo objetivou identificar a carga de trabalho de enfermagem em unidade de Terapia Intensiva de Cardiologia e verificar a associação dessa variável com características demográficas e clínicas dos pacientes. A amostra foi de 100 pacientes internados no período de agosto a setembro de 2006, na Unidade de Terapia Intensiva Cardiológica de um hospital privado, do Município de São Paulo. O Nursing Activities Score, o Symplified Acute Physiologic ScoreII e o Logistic Organ Disfunction System foram utilizados par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 19 publications
5
21
2
14
Order By: Relevance
“…Within the scope of cardiology, in the present study, the NAS obtained at 24 hours (82.4%) corresponds to 19.7 hours of work by the nursing staff per patient, a value greater in comparison to other medical specialties (7)(8)(9) and from another post-operative care unit for cardiac surgery (10) . Additionally, the NAS at 24 hours was greater than that at 72 hours.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Within the scope of cardiology, in the present study, the NAS obtained at 24 hours (82.4%) corresponds to 19.7 hours of work by the nursing staff per patient, a value greater in comparison to other medical specialties (7)(8)(9) and from another post-operative care unit for cardiac surgery (10) . Additionally, the NAS at 24 hours was greater than that at 72 hours.…”
Section: Discussionmentioning
confidence: 47%
“…The activities included in the NAS, which includes 23 items, portray the need for care of a seriously ill patient during the first 24 hours (5)(6) . Although the NAS is widely used in intensive care units (ICU) of different specialties (7)(8)(9) , its application in specific settings, such as postoperative care of cardiac surgery, is still limited (10)(11) . The NAS findings have indicated that sociodemographic (6)(7) and clinical variables, (7) length of stay in the ICU (11) , mortality (8) and severity of the patient's conditions (8,10,12) are factors associated with the high workload of the nursing staff.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aunque el NAS haya sido originalmente creado para ser usado en UCI, la evaluación de carga de trabajo basada en las actividades de enfermería, en diferentes contextos asistenciales, posibilita su uso en otras especialidades clínicas (9,10) . En la especialidad de Onco-Hematología son incipientes los estudios abordando carga de trabajo de enfermería, independiente del instrumento o método utilizado.…”
Section: Introductionunclassified